Congenital Rhabdomyosarcoma: a different clinical presentation in two cases - Ida Russo; Virginia Di Paolo; Carmelo Gurnari; Angela Mastronuzzi; Francesca Del Bufalo; Pier Luigi Di Paolo; Angela Di Giannatale; Renata Boldrini; Giuseppe Maria Milano (BMC, 2018)
Abstract Background Rhabdomyosarcoma (RMS), one of the most common soft tissue sarcomas of childhood, is very rare in the neonatal period (0.4-2% of cases). In order to gain a deeper understanding of this disease at such age, patient and tumor features, as well as treatment modality and outcome need to be reported. Case presentation We describe two cases with congenital RMS treated at Bambino Gesù Children's Hospital between 2000 and 2016. They represent only 2.24% of all RMS patients diagnosed during that period in our Institution; this data is in agreement with the incidence reported in the literature. They reflect the two different clinical forms in which the disease may manifest itself. One patient, with the alveolar subtype (positive for specific PAX3-FOXO1 fusion transcript) and disseminated disease, had a fatal outcome with central nervous system (CNS) progression despite conventional and high dose chemotherapy. The other child, with the localized embryonal subtype, was treated successfully with conservative surgery and conventional chemotherapy, including prolonged maintenance therapy. He is disease free at 7 years of follow-up. Conclusions RMS can also be diagnosed during the neonatal period. Given the young age, disease management is often challenging, and especially for the alveolar subtype, the outcome is dismal despite intensified multimodality therapy. In fact, it characteristically manifests with multiple subcutaneous nodules and progression most commonly occurs in the CNS (Rodriguez-Galindo et al., Cancer 92(6):1613-20, 2001). In this context, CNS prophylaxis could play a role in preventing leptomeningeal dissemination, and molecular studies can allow a deeper tumor characterization, treatment stratification and identification of new potential therapeutic targets.